Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1097/cin.0000000000000005
|View full text |Cite
|
Sign up to set email alerts
|

Computerized Provider Order Entry Awareness for Nursing

Abstract: Many healthcare facilities are in the process of implementing, or planning to implement, computerized provider order entry (CPOE). In this article, we share our experience of planning for and implementing CPOE. One of our goals was to avoid unintended consequences for nurses that at best require expensive changes after implementation or worst can create unsafe situations. We are a team of nursing informaticists at a 450-bed, not-for-profit, acute-care hospital with an emergency department/level I trauma center… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…6 Nurses, as care coordinators, are often described as the last line of defense between a patient and an error when gaps in communication and system inefficiencies arise. Nurses operate at "sharp-end" error intersections and are directly responsible for administering medications and/or choosing to initiate or delay treatments when errors occur.…”
mentioning
confidence: 99%
“…6 Nurses, as care coordinators, are often described as the last line of defense between a patient and an error when gaps in communication and system inefficiencies arise. Nurses operate at "sharp-end" error intersections and are directly responsible for administering medications and/or choosing to initiate or delay treatments when errors occur.…”
mentioning
confidence: 99%
“…Studies have revealed that healthcare workers' reluctance to embrace technology significantly limits their participation in eHealth activities. This is often due to their need for sufficient knowledge and skills to operate eHealth services, which results in denial and resistance towards information technologies [30][31][32]. Furthermore, the low usage of the internet among doctors in Pakistan is attributed to their insufficient IT skills.…”
Section: Factors Influencing the Integration And Use Of Ehealthmentioning
confidence: 99%
“…In a qualitative study on factors affecting the implementation of a standardized information system conducted in Cameroon, the findings showed that the centralized and bureaucratic organizational structure deters the allocation of finance to ICT-related activities, particularly at the lower level (district level) of the health system [17]. A study conducted by Staton et al indicates that resistance to change on the part of healthcare professionals hindered eHealth and limited involvement in eHealth standard development [18]. Similarly, Adebesin et al, [19] attributed low integration of eHealth to the inability of Health Information systems (HIS) to interoperate.…”
Section: Factors Influencing the Integration And Use Of Ehealthmentioning
confidence: 99%